Use spatial information in integrated inertial-satellite navigation systems of aircraft - A. I. Sokolov; Y. S. Yurchenko (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The tightly coupled integration with serial measurement processing of the pseudo ranges and carrier Doppler measurements is investigated. The spatial information of inertial navigation systems is used for determination satellite attitude relative to directional diagram and for signal search stoppage at the time of the flight maneuver.